CUSTOMER COMPLAINT BEHAVIOUR: A STUDY OF AIRLINE CUSTOMERS - Rajain, Pallavi (Innovare Journal of Social Sciences, 2016)
Unfavourable service experience causing dissatisfaction is believed to be the prerequisite of complaint behaviour. It is therefore vital for any service provider to understand the aspects of an unfavourable service experience in order to prevent damaging complaint behaviour.During service encounters, consumers expect zero-defects in service delivery. Despite the service provider's attempts to offer consistent, high-quality service to consumers, service failures may still occur because of the critical service characteristics. Therefore, an attempt has been made in this study to find the pre-board and on-board service attributes that the customers complain about when they are dissatisfied. Secondly the author tried to find the major problems that lead to complaints and finally find the actions taken by customers when they feel dissatisfied with the airline service. The study included a sample of 112 passengers who were randomly selected from the ones present at IGI Airport. SPSS version 23 was used for the purpose of analysis and finding descriptive statistics. It was found that the majority of respondents were likely to complain regarding the various services attributes mentioned in the questionnaire. The most important problem that influences the customer's decision to complain was cancellation in flight and the most common actions taken by customers when they feel dissatisfied with the airline service included seeking replacement for the service and spreading negative word of mouth. The paper focusses on the service attributes causing dissatisfaction among the customers and the mode of complaint being followed by them in order to deal with the problem.